Bewegungen Beiträge zum 26. Kongress der Deutschen Gesellschaft für Erziehungswissenschaft - van Ackeren, Isabell; Bremer, Helmut; Kessl, Fabian; Koller, Hans-Christoph; Pfaff, Nicolle; Rotter, Carolin; Klein, Esther Dominique; Salaschek, Ulrich (Schriften der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2020)
Bewegungen sind konstitutiv für das Pädagogische. Menschliche Entwicklungsprozesse, pädagogische Beziehungen wie pädagogische Organisationen sind nur als Veränderungen in der Zeit, als Bewegungen, denkbar. Fragen der Bewegungen im Kontext pädagogischen Handelns und dessen Reflexion wurden im Rahmen des 26. Kongresses der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) in den Blick genommen. Auf Basis der Kongressdebatten sind die Beiträge dieses Bandes entstanden.; Movements are fundamental to pedagogy and education. Processes of human development, educational / pedagogical relations, or educational institutions are only conceivable when we regard their changes over time-as movements. At the same instance, movements refer to the actions of collective actors, which can be observed in history as movements of enlightenment as well as movements of pedagogy and education. Conditions of education, as well as and care, are constantly in motion. They depend on transformation processes of a society and simultaneously contribute to forming them. Pedagogical and educational movements affect humans and society.